Financial Structure and Bankruptcy Risk in Japanese Companies - Suzuki, Sadahiko; Wright, Richard W. (Journal of International Business Studies, 1985)
Financial structure and the nature of financial risk in Japanese companies differ substantially from those of U.S. firms. As a result, the application of U.S. standards is likely to produce misleading conclusions for creditors, investors and competitors. This article examines the unique institutional relationships and the nature of debt and equity claims that are central to understanding financial risk in Japan. It reports the results of empirical testing of the types of measures that more accurately reflect bankruptcy risk in large Japanese firms. The findings indicate that measures of a company's social importance and the strength of its bank relationship may be more important at financially crucial moments than accounting information. The results are of practical value to foreign creditors and analysts, as well as to researchers.